A manual of diseases of eucalyptus in South-East Asia - Old, K.M.; Wingfield, M.J.; Zi Qing Yuan (Center for International Forestry Research, 2003)
Avoidance of major epidemics of eucalypt diseases in South-East Asia requires an increases awareness of the risks from pathogens, inherent in plantation forestry and a systematic approach to disease management. A good knowledge is needed of those diseases, present in plantations. Based on such knowledge, tree species, provenances and clones can be assessed for their susceptibility to major pathogens and strategies can be devised for the systematic deployment of different clones of widely varying parentage throughout plantation regions. Clonal forestry then has the potential to become a powerful means for the control of plantation diseases, as practised in Brazil and South Africa for eucalypt cankers, rather than increasing the risk of epidemics. This manual will be of assistance to those charged with maintaining the health of eucalypt plantations, in identifying the common diseases present in their region. It provides recommendations for disease management and offers an introduction to relevant world literature. The manual is a companion to the earlier CIFOR-published "A manual of diseases of tropical acacias in Australia, South-East Asia and India.